Flame-retardant semi-solid electrolyte, battery and preparation method

By adopting the preparation method of flame retardant semi-solid electrolyte in lithium-ion batteries, and using the combination of polymer frame and flame retardant plasticizer, the problem of thermal runaway in traditional lithium-ion batteries is solved, achieving high safety Lithium-ion batteries with long cycle life.

CN119419350APending Publication Date: 2025-02-11SOUTHWEST PETROLEUM UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566836.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries are prone to thermal runaway under extreme conditions such as overcharging, short circuit, extrusion and high temperatures, and their energy density is small, which cannot meet the needs of large-capacity lithium batteries.

Method used

Using a preparation method of flame retardant semi-solid electrolyte, the initiator is polymerized to polymerize the in-situ ring ether monomer, lithium salt, initiator, flame retardant plasticizing solvent, selective plasticizing co-solvent and additives by initiator in situ ring opening to polymer Porous support material, a flame-retardant semi-solid electrolyte is produced.

Benefits of technology

It achieves high safety and long cycle life of lithium-ion batteries, eliminates the combustion or thermal runaway problems that are easily caused by the battery under extreme conditions, and significantly improves the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419350A_ABST
    Figure CN119419350A_ABST
Patent Text Reader

Abstract

The invention provides a flame-retardant semi-solid electrolyte, a battery and a preparation method. The method comprises the following steps: preparing a cyclic ether monomer, a lithium salt, an initiator, a flame-retardant plasticizing solvent, a selective plasticizing cosolvent and an additive into a polymer precursor solution; the preparation method comprises the following steps: dropwise adding a polymer precursor solution on a polymer porous support material, and carrying out in-situ polymerization for 2-48 hours at 25-80 DEG C to obtain the flame-retardant semi-solid electrolyte which can be used for a lithium ion battery. The semi-solid electrolyte disclosed by the invention has high safety of flame retardance and leakage prevention, can remarkably improve the cycling stability and the rate capability, has high ionic conductivity, remarkably reduces the electrolyte cost by replacing an electrolyte solvent with low-cost polyether, and is easy to commercialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semi-solid polymer electrolytes, and in particular to a flame-retardant semi-solid electrolyte, a battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are new energy storage media with excellent characteristics such as high voltage, long cycle life, high specific capacity, low self-discharge, high safety, environmental protection, no pollution, and no memory effect. At present, lithium-ion batteries have been widely used in portable electronic devices such as mobile phones, laptops and digital products. With the continuous development of human society and the increasing depletion of non-renewable resources, lithium-ion batteries will definitely have broader application prospects in electric vehicles, hybrid vehicles, etc. However, traditional lithium-ion batteries have a small capacity and cannot meet people's urgent demand for large-capacity lithium batteries. The energy density of lithium-ion batteries mainly depends on the lithium storage capacity and voltage of the positive and negative electrode materials. At present, the commercial lithium-ion battery negative electrode material graphite has almost reached its theoretical lithium storage capacity (372mAh g -1 ). Lithium metal and silicon negative electrode materials have high theoretical specific capacity and are considered to be the next generation of lithium battery negative electrode materials. However, commercial lithium-ion battery electrolytes include low-boiling carbonate solvents and lithium hexafluorophosphate. Lithium-ion batteries using traditional commercial electrolytes are prone to thermal runaway under extreme conditions such as overcharge, short circuit, extrusion and high temperature. Therefore, it is urgent to develop a highly safe electrolyte for lithium-ion batteries. Summary of the invention

[0003] The purpose of the present invention is to solve at least one of the above-mentioned deficiencies in the prior art. For example, one of the purposes of the present invention is to provide a method for preparing a flame retardant semi-solid electrolyte; a second purpose of the present invention is to provide a flame retardant semi-solid electrolyte; a third purpose of the present invention is to provide a method for preparing a flame retardant semi-solid lithium ion battery; a fourth purpose of the present invention is to provide a flame retardant semi-solid lithium ion battery.

[0004] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing a flame retardant semi-solid electrolyte, the method comprising: in situ ring-opening polymerization of a plurality of raw materials on a polymer porous support material through an initiator to obtain a flame retardant semi-solid electrolyte; wherein the plurality of raw materials include: cyclic ether monomers, lithium salts, initiators, flame retardant plasticizing solvents, selective plasticizing co-solvents and additives.

[0005] Alternatively, the in-situ ring-opening polymerization of the multiple raw materials on the polymer porous support material by an initiator includes: preparing the multiple raw materials into a polymer precursor solution; dripping the polymer precursor solution on the polymer porous support material, and performing in-situ polymerization to obtain the flame-retardant semi-solid electrolyte. The in-situ polymerization temperature can be 25 to 80° C., and the time is 2 to 48 hours.

[0006] The second aspect of the present invention provides a method for preparing a flame-retardant semi-solid lithium-ion battery, the method comprising: assembling a lithium-ion battery in the order of a positive electrode shell, a positive electrode, a polymer porous support material to which a polymer precursor solution is dropped, a negative electrode, a steel sheet, a spring sheet, and a negative electrode shell, packaging the battery according to a set pressure, and in-situ polymerizing for 2 to 48 hours at 25 to 80° C. to obtain a flame-retardant semi-solid lithium-ion battery; wherein the polymer precursor solution is prepared from a cyclic ether monomer, a lithium salt, an initiator, a flame-retardant plasticizing solvent, a selective plasticizing co-solvent, and an additive.

[0007] According to the first aspect or the second aspect above, optionally, the mass fraction of the cyclic ether monomer in the polymer precursor solution may be 10 to 50%;

[0008] The mass fraction of the lithium salt in the polymer precursor solution may be 10 to 30%;

[0009] The mass fraction of the flame retardant plasticizer in the polymer precursor solution may be 10 to 50%;

[0010] The mass fraction of the selective plasticizing co-solvent in the polymer precursor solution may be 10 to 50%;

[0011] The mass fraction of the additive in the polymer precursor solution may be 1 to 10%;

[0012] The mass fraction of the initiator in the polymer precursor solution may be 0.1 to 30%.

[0013] According to the first aspect or the second aspect above, optionally, the polymer porous support material includes one of a PP membrane, a PE membrane, a GF / A fiber membrane, a GF / D fiber membrane, a PVDF electrospinning membrane, a PMMA electrospinning membrane, a PVDF-HFP electrospinning membrane, and a PAN electrospinning membrane.

[0014] According to the first aspect or the second aspect above, optionally, the cyclic ether monomer includes one or more of 1,3-dioxane, 1,3,5-trioxane, tetrahydrofuran and 1,3-dioxane.

[0015] Preferably, the cyclic ether monomer is 1,3,5-trioxane.

[0016] According to the first aspect or the second aspect above, optionally, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium dioxalatoborate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate and lithium difluorobis(oxalatophosphate).

[0017] Preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl imide).

[0018] According to the first aspect or the second aspect above, optionally, the initiator includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, stannous trifluoromethanesulfonate, stannous fluoride, tin fluoride, aluminum trifluoromethanesulfonate, aluminum fluoride, aluminum chloride, aluminum bromide and aluminum iodide.

[0019] Preferably, the initiator is lithium difluorooxalatoborate.

[0020] According to the first aspect or the second aspect above, optionally, the flame retardant plasticizing solvent includes one or more of trimethyl phosphate, triethyl phosphate, triallyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, diethyl phenylphosphonate, tris(2,2,2-trifluoroethyl) phosphate, tris(2,2,2-trifluoroethyl) borate, tris(2,2,2-trifluoroethyl) phosphite, 4-trifluoromethylethylene carbonate, hexafluorocyclotriphosphazene, ethoxy(pentafluoro)cyclotriphosphazene, pentafluoro(phenoxy)cyclotriphosphazene and hexa(2,2,2-trifluoroethoxy)cyclotriphosphazene.

[0021] Preferably, the flame retardant plasticizing solvent is triethyl phosphate.

[0022] According to the above-mentioned first aspect or second aspect, optionally, the selective plasticizing co-solvent comprises one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, methyl propyl carbonate, fluoroethylene carbonate, vinylene carbonate, vinylene carbonate, ethylene ethylene carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, methyl trifluoroethyl carbonate and di(2,2,2-trifluoroethyl) carbonate.

[0023] Preferably, the selective plasticizing co-solvent is fluoroethylene carbonate.

[0024] According to the first aspect or the second aspect above, optionally, the additive includes one or more of tris(trimethylsilyl)phosphite, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate and 1-trimethylbenzenesulfonyl-1,2,4-triazole.

[0025] Preferably, the additive is tris(trimethylsilyl) phosphate.

[0026] According to the above second aspect, optionally, the positive electrode includes a positive electrode sheet material, and the positive electrode sheet material includes one of lithium iron phosphate, nickel-cobalt-manganese ternary positive electrode material, nickel-cobalt-aluminum ternary positive electrode material, lithium cobalt oxide and lithium nickel manganese oxide.

[0027] According to the above second aspect, optionally, the negative electrode includes a negative electrode sheet material, and the negative electrode sheet material includes one of lithium metal, graphite material, lithium titanate, pure silicon material, silicon / carbon composite material, silicon oxide, silicon oxide / carbon composite material, lithium silicate / silicon / carbon composite material and magnesium silicate / silicon / carbon composite material.

[0028] A third aspect of the present invention provides a flame retardant semi-solid electrolyte.

[0029] The flame retardant semi-solid electrolyte can be prepared by the method of the first aspect mentioned above.

[0030] A fourth aspect of the present invention provides a method for preparing a flame retardant semi-solid lithium ion battery, wherein the battery comprises using the flame retardant semi-solid electrolyte of the third aspect to prepare the battery.

[0031] A fifth aspect of the present invention provides a flame retardant semi-solid lithium ion battery.

[0032] The flame retardant semi-solid lithium ion battery can be prepared by the method of the second aspect mentioned above.

[0033] Compared with the prior art, the beneficial effects of the present invention include at least one of the following:

[0034] (1) The semi-solid electrolyte prepared by the method of the present invention uses ether monomers as the polymer framework and has excellent ionic conductivity and ion migration number; the polyether polymer can infiltrate the negative electrode of the lithium-ion battery, provide cohesive force between the negative electrode materials, inhibit volume expansion, and thus improve the cycle life.

[0035] (2) The present invention uses a flame retardant plasticizer in combination with an intrinsically flammable polyether polymer, thereby eliminating the problem that the electrolyte can easily cause battery combustion or thermal runaway under extreme conditions, thereby improving the safety of semi-solid lithium-ion batteries.

[0036] (3) The selective co-solvent plasticizer introduced in the present invention can form a stable SEI film to improve the performance of the negative electrode of the lithium ion battery; the addition of the additive can control the polymerization of the polymer by inhibiting the decomposition activity of the initiator and improve the degree of polymerization of the polymer, and on the other hand, further improve the performance of the lithium ion battery by forming a stable SEI film on the surface of the negative electrode.

[0037] (4) The method of the present invention has low preparation cost and is simple and easy to implement; the prepared electrolyte is highly safe and can ensure the operation of the battery under extreme conditions, thus promoting the further development of lithium-ion batteries.

[0038] (5) After the semi-solid electrolyte prepared by the present invention is polymerized by cyclic ether, the liquid component is fixed in the polymer framework, the amount of volatile solvent is significantly reduced, and it has high safety of flame retardancy and leakage prevention.

[0039] (6) The semi-solid electrolyte of the present invention significantly improves cycle stability and rate performance and has high ionic conductivity. Replacing the electrolyte solvent with low-cost polyether significantly reduces the electrolyte cost and is easy to commercialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The above and other objects and / or features of the present invention will become more apparent through the following description in conjunction with the accompanying drawings, in which:

[0041] Figure 1 The figure shows the state comparison of the semi-solid electrolytes prepared in Example 1 and Example 2 of the present invention before and after polymerization;

[0042] Figure 2 The ignition test results of the electrolyte prepared in Comparative Example 2 of the present invention are shown;

[0043] Figure 3 The ignition test results of the flame retardant semi-solid electrolyte prepared in Example 2 of the present invention are shown;

[0044] Figure 4 The figure shows the morphology of the electrolyte lithium deposited on the copper foil surface prepared in Comparative Example 1 of the present invention;

[0045] Figure 5 The figure shows the morphology of the electrolyte lithium deposited on the copper foil surface prepared in Comparative Example 2 of the present invention;

[0046] Figure 6 The figure shows the morphology of the semi-solid electrolyte lithium deposited on the surface of the copper foil prepared in Example 2 of the present invention;

[0047] Figure 7 The cycle performance of the lithium iron phosphate half-cell assembled with the semi-solid electrolyte prepared in Example 2 of the present invention is shown;

[0048] Figure 8 The figure shows the rate performance of the lithium iron phosphate half-cell assembled with the semi-solid electrolyte prepared in Example 2 of the present invention;

[0049] Fig. 9 The first charge and discharge performance of the silicon dioxide / carbon half-cell assembled with the semi-solid electrolyte prepared in Example 2 of the present invention is shown. DETAILED DESCRIPTION

[0050] Hereinafter, the flame retardant semi-solid electrolyte, battery and preparation method of the present invention will be described in detail in conjunction with exemplary embodiments.

[0051] The commonly constructed semi-solid battery uses a liquid organic solvent composite polymer matrix to form a semi-solid electrolyte, which can effectively solve the interface contact problem and reduce the interface resistance. Semi-solid polymer electrolytes are usually prepared by in-situ polymerization initiation or immersing the polymer film in a liquid electrolyte. Therefore, the obtained semi-solid polymer electrolyte has high ionic conductivity and low interface resistance, and has the advantages of high mechanical strength, easy processing and high flexibility, which can effectively ensure the stable operation of the battery. However, the semi-solid electrolyte is still flammable and contains organic solvents, so replacing the organic solvent with a flame retardant can effectively improve its safety. Under the comprehensive balance of factors such as safety, energy density, power density, cycle life, high temperature and low temperature, semi-solid batteries are expected to be commercialized first because they are compatible with most materials, equipment and processes of liquid lithium batteries.

[0052] The use of flame-retardant semi-solid electrolytes combines the advantages of flame retardants and polymer electrolytes. The polyether monomer infiltrates the negative electrode of the lithium-ion battery in the precursor solution, provides cohesion after polymerization to adapt to the volume change of the negative electrode of the lithium-ion battery during the cycle, and continuously increases the ionic conductivity to improve the electrochemical performance and stability; flame retardants are used to eliminate the flammability of traditional commercial electrolytes and improve the safety of batteries. However, simple mixing and polymerization cannot guarantee the appropriate degree of polymerization and stability of lithium-ion batteries, resulting in a decrease in ionic conductivity and a rapid attenuation of battery capacity. Therefore, the synergistic effect of polyether monomers, flame-retardant plasticizers, co-solvent plasticizers compatible with the positive and negative electrodes of lithium-ion batteries, and siloxane additives for adjusting the degree of polymerization are used to ensure the high safety performance and long cycle performance of lithium-ion batteries.

[0053] Exemplary Embodiment 1

[0054] This exemplary embodiment provides a method for preparing a flame retardant semi-solid electrolyte, the method comprising:

[0055] A flame retardant semi-solid electrolyte is prepared by in-situ ring-opening polymerization of a plurality of raw materials on a polymer porous support material through an initiator; wherein the plurality of raw materials include: cyclic ether monomers, lithium salts, initiators, flame retardant plasticizing solvents, selective plasticizing co-solvents and additives.

[0056] In this embodiment, the in-situ ring-opening polymerization of the multiple raw materials on the polymer porous support material by an initiator includes:

[0057] preparing the plurality of raw materials into a polymer precursor solution;

[0058] The polymer precursor solution is dripped onto the polymer porous support material to perform in-situ polymerization to obtain the flame-retardant semi-solid electrolyte.

[0059] Wherein, the temperature of the in-situ polymerization is 25-80° C., and the time is 2-48 hours.

[0060] Preferably, the temperature is 60° C. and the time is 20 h. The purpose of selecting the above temperature and time range is that the initiator completely decomposes at this temperature to initiate polymerization of the polymer precursor solution, and the polymerization reaction completely occurs within this time.

[0061] In this embodiment, the mass fraction of the cyclic ether monomer in the polymer precursor solution is 10 to 50%;

[0062] The mass fraction of the lithium salt in the polymer precursor solution is 10 to 30%;

[0063] The mass fraction of the flame retardant plasticizer in the polymer precursor solution is 10 to 50%;

[0064] The mass fraction of the selective plasticizing co-solvent in the polymer precursor solution is 10 to 50%;

[0065] The mass fraction of the additive in the polymer precursor solution is 1 to 10%;

[0066] The mass fraction of the initiator in the polymer precursor solution is 0.1-30%.

[0067] In this embodiment, the polymer porous support material includes one of PP membrane, PE membrane, GF / A fiber membrane, GF / D fiber membrane, PVDF electrospinning membrane, PMMA electrospinning membrane, PVDF-HFP electrospinning membrane, and PAN electrospinning membrane.

[0068] In this embodiment, the cyclic ether monomer includes one or more of 1,3-dioxolane (DOL), 1,3,5-trioxane (TXE), tetrahydrofuran (THF) and 1,3-dioxane (DOX).

[0069] Preferably, the cyclic ether monomer is 1,3,5-trioxane (TXE), and the role of the cyclic ether monomer is to provide a polymer framework precursor.

[0070] In this embodiment, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium perchlorate (LiClO4) and lithium difluorobis(oxalatophosphate) (LiDFBOP).

[0071] Preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and the lithium salt mainly functions to provide lithium ions.

[0072] In this embodiment, the initiator includes one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), stannous trifluoromethanesulfonate (Sn(OTf)2), stannous fluoride (SnF2), tin fluoride (SnF4), aluminum trifluoromethanesulfonate (Al(OTf)3), aluminum fluoride (AlF3), aluminum chloride (AlCl3), aluminum bromide (AlBr3) and aluminum iodide (AlI3).

[0073] Preferably, the initiator is lithium difluorooxalatoborate (LiDFOB), and the function of the initiator is to initiate polymerization of monomers into a polymer framework by heating.

[0074] In this embodiment, the flame retardant plasticizing solvent includes one or more of trimethyl phosphate (TMP), triethyl phosphate (TEP), triallyl phosphate (TAP), tributyl phosphate (TBP), trioctyl phosphate (TOP), triphenyl phosphate (TPP), diethyl phenylphosphonate (DEPP), tris(2,2,2-trifluoroethyl) phosphate (TFEP), tris(2,2,2-trifluoroethyl) borate (TTFEB), tris(2,2,2-trifluoroethyl) phosphite (TTFP), 4-trifluoromethylethylene carbonate (TFPC), hexafluorocyclotriphosphazene (HFPN), ethoxy(pentafluoro)cyclotriphosphazene (PFPN), pentafluoro(phenoxy)cyclotriphosphazene (FPPN) and hexa(2,2,2-trifluoroethoxy)cyclotriphosphazene (HFEPN).

[0075] Preferably, the flame retardant plasticizer solvent is triethyl phosphate (TEP), and the flame retardant plasticizer has the function of providing flame retardancy.

[0076] In this embodiment, the selective plasticizing co-solvent includes one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), methyl propyl carbonate (MPC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (DEE), tetraethylene glycol dimethyl ether (G4), 1,3-dioxolane (DOL), methyl trifluoroethyl carbonate (FEMC) and bis(2,2,2-trifluoroethyl) carbonate (TFEC).

[0077] Preferably, the selective plasticizing co-solvent is fluoroethylene carbonate (FEC), and the function of the selective plasticizer is to provide stability for the positive and negative electrodes of the lithium-ion battery.

[0078] In this embodiment, the additive includes one or more of tris(trimethylsilyl)phosphite (TMSPi), tris(trimethylsilyl)phosphate (TMSPa), tris(trimethylsilyl)borate (TMSB) and 1-trimethylbenzenesulfonyl-1,2,4-triazole (TMST).

[0079] Preferably, the additive is tris(trimethylsilyl) phosphate (TMSPa), and the function of the additive is to improve the polymer structure and provide lithium ion positive and negative electrode stability.

[0080] Exemplary Embodiment 2

[0081] The present exemplary embodiment provides a flame retardant semi-solid electrolyte.

[0082] The flame retardant semi-solid electrolyte is prepared by the method described in Exemplary Embodiment 1.

[0083] Exemplary Embodiment 3

[0084] This exemplary embodiment provides a flame-retardant semi-solid lithium-ion battery, which includes the flame-retardant semi-solid electrolyte described in Exemplary Embodiment 2.

[0085] Example 4

[0086] This exemplary embodiment provides a method for preparing a flame-retardant semi-solid lithium-ion battery. The preparation method comprises:

[0087] The battery is assembled in the order of positive electrode shell, positive electrode, polymer porous support material with polymer precursor solution added, negative electrode, steel sheet, spring sheet and negative electrode shell, and the battery is packaged according to the set pressure; at 25-80° C., in-situ polymerization is carried out for 2-48 hours to obtain a flame-retardant semi-solid lithium-ion battery.

[0088] The polymer precursor solution is prepared from cyclic ether monomers, lithium salts, initiators, flame retardant plasticizing solvents, selective plasticizing co-solvents and additives. The types of cyclic ether monomers, lithium salts, initiators, flame retardant plasticizing solvents, selective plasticizing co-solvents and additives are the same as those in Example 1, and the proportion of each raw material in the polymer precursor solution is also the same as that in Example 1.

[0089] In this embodiment, the positive electrode includes a positive electrode sheet material, and the positive electrode sheet material includes one of lithium iron phosphate, nickel-cobalt-manganese ternary positive electrode material, nickel-cobalt-aluminum ternary positive electrode material, lithium cobalt oxide and lithium nickel manganese oxide.

[0090] In this embodiment, the negative electrode includes a negative electrode sheet material, and the negative electrode sheet material includes one of lithium metal, graphite negative electrode, lithium titanate, pure silicon material, silicon / carbon composite material, silicon oxide, silicon oxide / carbon composite material, lithium silicate / silicon / carbon composite material and magnesium silicate / silicon / carbon composite material.

[0091] Exemplary Embodiment 5

[0092] The present exemplary embodiment provides a flame retardant semi-solid lithium ion battery.

[0093] The flame-retardant semi-solid lithium-ion battery can be prepared by the method described in Exemplary Embodiment 3 or Exemplary Embodiment 4.

[0094] In order to better understand the above exemplary embodiments, further description is given below with reference to specific examples.

[0095] Example 1

[0096] (1) 1,3,5-trioxane was dissolved in triethyl phosphate and fluoroethylene carbonate (the volume ratio of triethyl phosphate and fluoroethylene carbonate was 5:5) in a mass ratio of 4:6, and stirred for 10 hours to obtain a first mixture; (2) 0.344 g of lithium salt lithium bis(trifluoromethanesulfonyl imide) and 0.115 g of initiator salt lithium difluorooxalatoborate were added to 2 g of the first mixture, and stirred for 5 hours to obtain a second mixture; (3) Preparation of the negative electrode: The negative electrode material (silicon oxide / carbon), conductive agent, and binder were mixed in a mass ratio of 8:1:1, the mixture was evenly ground, and then coated on a copper foil, and then heated for 6 hours. The battery was dried in an oven at 5°C for 12 h to obtain a negative electrode sheet for use in the battery; (4) Preparation of the positive electrode: The positive electrode material (lithium iron phosphate), conductive agent, and binder were mixed in a mass ratio of 8:1:1, the mixture was evenly ground and coated on an aluminum foil, and the mixture was dried in an oven at 65°C for 12 h to obtain a positive electrode sheet for use in the battery; (5) Assembly of semi-solid polymer batteries: Batteries were assembled in the order of different battery types, 70 μL of the second mixture was added to wet the polymer porous support material PE diaphragm, the battery was encapsulated, and then in-situ polymerized in an oven at 60°C for 20 h to obtain a semi-solid polymer electrolyte and a semi-solid battery containing an electrolyte.

[0097] Example 2

[0098] (1) 1,3,5-trioxane was dissolved in triethyl phosphate and fluoroethylene carbonate (the volume ratio of triethyl phosphate and fluoroethylene carbonate was 5:5) in a mass ratio of 4:6, and stirred for 10 hours to obtain a first mixture; (2) 0.344g of lithium salt lithium bis(trifluoromethanesulfonyl)imide and 0.115g of initiator salt lithium difluorooxalatoborate were added to 2g of the first mixture, and stirred for 5 hours to obtain a second mixture; (3) 2% by mass of the additive tris(trimethylsilyl) phosphate was added to the second mixture to obtain a third mixture; (4) Preparation of the negative electrode: the negative electrode material (silicon oxide / carbon), the conductive agent, and the binder were mixed in a mass ratio of 8:1:1. The mixture was mixed, ground evenly, and coated on copper foil. The mixture was dried in an oven at 65°C for 12 h to obtain a negative electrode sheet for the battery; (5) Preparation of positive electrode: The positive electrode material (lithium iron phosphate), conductive agent, and binder were mixed in a mass ratio of 8:1:1, ground evenly, and coated on aluminum foil. The mixture was dried in an oven at 65°C for 12 h to obtain a positive electrode sheet for the battery; (6) Assembly of semi-solid polymer batteries: Batteries were assembled in the order of different battery types, 70 μL of the third mixture was added to wet the polymer porous support material PE diaphragm, and the battery was encapsulated and in situ polymerized in an oven at 60°C for 20 h to obtain a semi-solid polymer electrolyte and a semi-solid battery containing an electrolyte.

[0099] Example 3

[0100] An electrolyte and a lithium ion battery including the electrolyte of this embodiment were obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 was changed to 0:10, and the other steps were the same as Example 1.

[0101] Example 4

[0102] An electrolyte and a lithium ion battery including the electrolyte of this embodiment were obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 was changed to 1:9, and the other steps were the same as Example 1.

[0103] Example 5

[0104] An electrolyte and a lithium ion battery including the electrolyte of this embodiment were obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 was changed to 2:8, and the other steps were the same as Example 1.

[0105] Example 6

[0106] An electrolyte and a lithium ion battery including the electrolyte of this embodiment are obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 is changed to 3:7, and the other steps are the same as Example 1.

[0107] Example 7

[0108] An electrolyte and a lithium ion battery including the electrolyte of this embodiment were obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 was changed to 4:6, and the other steps were the same as Example 1.

[0109] Example 8

[0110] An electrolyte and a lithium ion battery including the electrolyte of this embodiment were obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 was changed to 6:4, and the other steps were the same as Example 1.

[0111] Example 9

[0112] An electrolyte and a lithium ion battery including the electrolyte of this embodiment were obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 was changed to 7:3, and the other steps were the same as Example 1.

[0113] Example 10

[0114] An electrolyte and a lithium ion battery including the electrolyte of this embodiment were obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 was changed to 8:2, and the other steps were the same as Example 1.

[0115] Embodiment 11

[0116] An electrolyte and a lithium ion battery including the electrolyte of this embodiment are obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 is changed to 9:1, and the other steps are the same as Example 1.

[0117] Example 12

[0118] An electrolyte and a lithium ion battery including the electrolyte of this embodiment were obtained according to the method of Example 1, except that the volume ratio of triethyl phosphate and fluoroethylene carbonate in Example 1 was changed to 10:0, and the other steps were the same as Example 1.

[0119] Comparative Example 1

[0120] (1) 0.344 g of lithium salt lithium bis(trifluoromethanesulfonyl imide) and 0.115 g of initiator salt lithium difluorooxalate borate were dissolved in a mixed solvent of 2 g of triethyl phosphate and fluoroethylene carbonate (the volume ratio of triethyl phosphate and fluoroethylene carbonate was 1:1), and stirred for 10 h to obtain a first mixture; (2) Comparative Example 1 battery assembly: Batteries were assembled in the order of different battery types, 70 μL of the first mixture was added dropwise to soak the polymer porous support material PE diaphragm, and the battery was encapsulated to obtain a comparative example 1 battery.

[0121] Comparative Example 2

[0122] (1) Comparative Example 2 provides a commercial electrolyte, specifically 1 mol / L LiPF6 / EC:EMC (volume ratio 3:7); (2) Comparative Example 2 battery assembly: assemble the batteries in the order of different battery types, add 70 μL of the electrolyte of Comparative Example 2 to infiltrate the polymer porous supporting material PE diaphragm, and encapsulate the battery to obtain the Comparative Example 2 battery.

[0123] Table 1 Electrolyte precursor solution formula

[0124]

[0125]

[0126] Table 2 Solvency, flame retardancy and performance of polymerized electrolyte lithium salt

[0127]

[0128] The performance test is screened by monomer solubility-lithium salt solubility-flame retardant properties-cycle performance after positive electrode selection. First, the monomer solubility is verified. After the monomer is dissolved, the next step of lithium salt dissolution is entered, otherwise the experiment of this embodiment is stopped; the flame retardant test is entered only after the lithium salt solubility is successfully verified, otherwise the experiment is stopped; after passing the flame retardant test, the long cycle battery performance test is entered.

[0129] The blank part indicates that the experimental process has been terminated in advance through experimental selection. Finally, Examples 1, 2, 7, and 8 are screened out based on the solubility and flame retardant properties of the electrolyte lithium salt after polymerization, and Example 2 is the best in terms of performance.

[0130] Comparison of Examples 1 and 2 before and after polymerization showed that Figure 1 As shown. Figure 1 It can be seen that the polymer modified by the additives can still be polymerized.

[0131] The comparative example 2 and the example 2 were subjected to ignition test to determine the flame retardant properties. The results are as follows: Figures 2-3 As shown. Figure 2 and Figure 3It can be seen that the commercial electrolyte will continue to burn after ignition, while the semi-solid electrolyte of Example 2 will not burn even if it is continuously ignited, and the flame will go out after the fire source is removed, indicating good flame retardant properties.

[0132] The electrolytes of Comparative Examples 1 to 2 and Example 2 were subjected to lithium deposition, and the deposition morphology was tested. The results are as follows: Figures 4 to 6 The specific deposition method is as follows: a metal lithium sheet with a diameter of 16 mm and a thickness of 0.6 mm is used as the negative electrode, a copper foil is used as the positive electrode, and a PE separator is used at a flow rate of 1 mA cm -2 The deposition was carried out under the conditions of, and the electrolytes were the electrolytes of Comparative Examples 1-2 and Example 2 respectively. Figures 5 to 7 It can be seen that the carbonate in the commercial electrolyte of Comparative Example 2 is prone to dendritic deposition and is easy to break to produce dead lithium. The liquid component of Comparative Example 1 that has not been modified by the polymer shows tubular deposition, which is loose and not dense. The semi-solid electrolyte of Example 2 produces large-particle block deposition, which is relatively uniform and has no obvious dendrites.

[0133] The semi-solid electrolyte of Example 2 was assembled into a lithium iron phosphate positive electrode half-cell, and the cycle performance and rate performance of the battery were tested. The results are as follows Figures 7-8 As shown. Figure 7 It can be seen that after 3 cycles of activation at C / 10, long cycles at C / 2 were performed, and the capacity retention rate after 200 cycles was 92.8%. Figure 8 It can be seen that when charging at a constant current of C / 3, the discharge capacity at C / 10 is 160 mAhg -1 , 156mAh g at C / 5 -1 , 152mAh g at C / 2 -1 , 148mAh g at 1C -1 , 124mAh g at 2C -1 .

[0134] The semi-solid electrolyte of Example 2 was assembled into a silicon oxide / carbon negative electrode half-cell, and the cycle performance of the cell was tested. The results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the first charge and discharge performance of the electrolyte of Example 2 of the present invention in the button cell is -1 The discharge capacity at the current density is 2568 mAh g -1 , charging capacity is 1899mAh g -1 , the first coulombic efficiency is 74%; this result can illustrate that the semi-solid electrolyte of Example 2 of the present invention has good adaptability to the negative electrode of the lithium-ion battery and can stably exert the charge and discharge energy.

[0135] Although the present invention has been described above in conjunction with the exemplary embodiments and the accompanying drawings, it should be apparent to those skilled in the art that various modifications may be made to the above-described embodiments without departing from the spirit and scope of the claims.

Claims

1. A method for preparing a flame retardant semi-solid electrolyte, characterized in that: The method comprises: A flame-retardant semi-solid electrolyte is prepared by in-situ ring-opening polymerization of various raw materials on a polymer porous support material through an initiator; The multiple raw materials include: cyclic ether monomers, lithium salts, initiators, flame retardant plasticizing solvents, selective plasticizing co-solvents and additives.

2. The method for preparing a flame retardant semi-solid electrolyte according to claim 1, characterized in that: The in-situ ring-opening polymerization of the various raw materials on the polymer porous support material by an initiator comprises: preparing the plurality of raw materials into a polymer precursor solution; The polymer precursor solution is dripped onto the polymer porous support material, and in-situ polymerization is carried out for 2 to 48 hours at 25 to 80° C. to obtain the flame-retardant semi-solid electrolyte.

3. A method for preparing a flame retardant semi-solid lithium ion battery, characterized in that: The assembly method comprises: Assembling a lithium-ion battery in the order of a positive electrode shell, a positive electrode, a polymer porous support material with a polymer precursor solution added thereto, a negative electrode, a steel sheet, a spring sheet, and a negative electrode shell, encapsulating the battery at a set pressure, and performing in-situ polymerization at 25 to 80° C. for 2 to 48 hours to obtain a flame-retardant semi-solid lithium-ion battery; The polymer precursor solution is prepared from cyclic ether monomers, lithium salts, initiators, flame retardant plasticizing solvents, selective plasticizing co-solvents and additives.

4. The preparation method according to claim 1 or 3, characterized in that: The mass fraction of the cyclic ether monomer in the polymer precursor solution is 10 to 50%; The mass fraction of the lithium salt in the polymer precursor solution is 10 to 30%; The mass fraction of the flame retardant plasticizer in the polymer precursor solution is 10 to 50%; The mass fraction of the selective plasticizing co-solvent in the polymer precursor solution is 10 to 50%; The mass fraction of the additive in the polymer precursor solution is 1 to 10%; The mass fraction of the initiator in the polymer precursor solution is 0.1-30%.

5. The preparation method according to claim 1 or 3, characterized in that: The polymer porous supporting material comprises one of a PP membrane, a PE membrane, a GF / A fiber membrane, a GF / D fiber membrane, a PVDF electrospinning membrane, a PMMA electrospinning membrane, a PVDF-HFP electrospinning membrane and a PAN electrospinning membrane.

6. The preparation method according to claim 1 or 3, characterized in that: The cyclic ether monomer includes one or more of 1,3-dioxolane, 1,3,5-trioxane, tetrahydrofuran and 1,3-dioxane; The lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium dioxalatoborate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate and lithium difluorobis(oxalatophosphate); The initiator includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, stannous trifluoromethanesulfonate, stannous fluoride, stannous fluoride, aluminum trifluoromethanesulfonate, aluminum fluoride, aluminum chloride, aluminum bromide and aluminum iodide.

7. The preparation method according to claim 1 or 3, characterized in that: The flame retardant plasticizing solvent comprises one or more of trimethyl phosphate, triethyl phosphate, triallyl phosphate, tributyl phosphate, trioctyl phosphate, triphenyl phosphate, diethyl phenylphosphonate, tris(2,2,2-trifluoroethyl) phosphate, tris(2,2,2-trifluoroethyl) borate, tris(2,2,2-trifluoroethyl) phosphite, 4-trifluoromethylethylene carbonate, hexafluorocyclotriphosphazene, ethoxy(pentafluoro)cyclotriphosphazene, pentafluoro(phenoxy)cyclotriphosphazene and hexa(2,2,2-trifluoroethoxy)cyclotriphosphazene; The selective plasticizing co-solvent comprises one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, methyl propyl carbonate, fluoroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, methyl trifluoroethyl carbonate and bis(2,2,2-trifluoroethyl) carbonate; The additive includes one or more of tris(trimethylsilyl)phosphite, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate and 1-trimethylbenzenesulfonyl-1,2,4-triazole.

8. A flame retardant semi-solid electrolyte, characterized in that: The flame retardant semi-solid electrolyte is prepared by the method according to claim 1 or 2.

9. The method for preparing a flame retardant semi-solid lithium ion battery according to claim 3, characterized in that: The positive electrode includes a positive electrode sheet material, and the positive electrode sheet material includes one of lithium iron phosphate, nickel-cobalt-manganese ternary positive electrode material, nickel-cobalt-aluminum ternary positive electrode material, lithium cobalt oxide and lithium nickel-manganese oxide; The negative electrode includes a negative electrode sheet material, and the negative electrode sheet material includes one of lithium metal, graphite material, lithium titanate, pure silicon material, silicon / carbon composite material, silicon oxide, silicon oxide / carbon composite material, lithium silicate / silicon / carbon composite material and magnesium silicate / silicon / carbon composite material.

10. A flame retardant semi-solid lithium ion battery, characterized in that: The battery comprises the flame retardant semi-solid electrolyte of claim 8 or is prepared by the method of claim 3.